Efficacy and safety of single-session radiofrequency ablation for intrathoracic goiter: preliminary results and short-term evaluation. (1st January 2021) - Chiang, Pi-Ling; Lin, Wei-Che; Chen, Hsiu-Ling; Luo, Sheng-Dean; Chen, Meng-Hsiang; Chen, Wei-Chih; Chang, Yen-Hsiang; Chou, Chen-Kai; Su, Yan-Ye; Tung, Yu-Cheng; Chen, Wen-Chieh; Chi, Shun-Yu; et al.
Abstract: Background: An intrathoracic goiter (ITG) is defined as a thyroid extension below the sternal notch. Compared to cervical goiters, surgery for ITG is more challenging, with a higher risk of an extracervical approach. Ultrasound (US)-guided radiofrequency ablation (RFA) is a minimally invasive treatment modality. The purpose of this study was to prospectively evaluate the safety and efficacy of RFA in patients with ITG. Methods: From a total of 324 patients who underwent thyroid RFA at a single medical center, 15 patients (mean age 52.2 years; 73.3% female) with 16 ITGs were included and classified into three grades and three types using the cross-section imaging CT system. Clinical features and demographics, degree of extension, RFA details, goiter volume, and complications were analyzed. Results: Mean pre- and post-RFA goiter volumes as measured by US were 106.62 ± 61.82 and 25.09 ± 14.22 mL respectively, with a volume reduction rate (VRR) of 75.5% ( p  < 0.001) at 6 months. The VRR as measured by CT/MRI was 57.0 ± 10.0% ( p  < 0.001) at 6 months. The intrathoracic length reduction rate at 6 months was 44.9 ± 39.2% ( p  = 0.001). In addition, 4 (25%) ITGs had total regression of the intrathoracic extension, with a downgrade from grade 1 to cervical goiter. Mean pre- and post-RFA symptom and cosmetic scores were 1.53 and 0.15 ( p  = 0.001), and 2.67 and 2.00 ( p  = 0.001), respectively. One patient had transient vocal cord palsy and another had perithyroidal and mediastinal hemorrhage. Conclusion: US-guided RFA is an effective treatment for ITG in terms of both cervical and intrathoracic reductions with an acceptable complication rate.